Znajomość zasad gwarantowania depozytów a skłonność do runu na banki - Kurowski, Łukasz; Górski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The main goal of the deposit guarantee scheme is to prevent banking panic and consequently to prevent banking crises. The purpose of the article is to check whether the knowledge of depositors about the existence of a deposit guarantee scheme and about the terms of the guarantee affects the propensity to bank run. Thus, the presented study emphasizes that the effectiveness of the deposit guarantee scheme is dependent on the degree of knowledge about the principles of its functioning insociety. The results of 200 CATI interviews suggest that this knowledge does not affect the decision to run on a bank, but determines the run type. People with higher knowledge about the principles of deposit guarantee are more likely to make a non-cash form of run (transfer of funds to another bank). For people with less knowledge the cash withdrawal is dominant. Due to the finite cash resources in bank branches, the cash withdrawal form can increase the scale of the run through its mediality.
Keywords: financial education; bank run; guarantee scheme